2019
DOI: 10.7554/elife.48767
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Sertoli-like cells from human fibroblasts by NR5A1 and GATA4

Abstract: Sertoli cells are essential nurse cells in the testis that regulate the process of spermatogenesis and establish the immune-privileged environment of the blood-testis-barrier (BTB). Here, we report the in vitro reprogramming of fibroblasts to human induced Sertoli-like cells (hiSCs). Initially, five transcriptional factors and a gene reporter carrying the AMH promoter were utilized to obtain the hiSCs. We further reduce the number of reprogramming factors to two, NR5A1 and GATA4, and show that these hiSCs have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 62 publications
(88 reference statements)
1
37
0
Order By: Relevance
“…The fundamental endocrine factors regulating testicular functions are LH, testosterone and FSH in mammals (Ramaswamy & Weinbauer, 2014). Spermatogenesis is initiated when LH from the pituitary activates the Leydig cell to produce testosterone which then acts in conjunction with FSH (O'Shaughnessy, 2014) to stimulate the Sertoli cell relevant in all aspect of spermatogenesis (Jones, 2014) and facilitates germ cells progression to spermatozoa and in the nourishment of developing sperm cells (Griswold, 1998, 2018; Liang et al., 2019). Testicular activities of LDH, ALP and ACP are important in the maintenance of normal germ cell growth and phosphorylative role in glucose usage by germ cells during spermatogenesis (Akhigbe & Ajayi, 2020; Motawi, Sadik, & Refaat, 2010; Rizk, Zaki, & Mina, 2014), while G6PD is essential for providing reducing equivalent necessary for steroidogenesis (Aly & Khafagy, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The fundamental endocrine factors regulating testicular functions are LH, testosterone and FSH in mammals (Ramaswamy & Weinbauer, 2014). Spermatogenesis is initiated when LH from the pituitary activates the Leydig cell to produce testosterone which then acts in conjunction with FSH (O'Shaughnessy, 2014) to stimulate the Sertoli cell relevant in all aspect of spermatogenesis (Jones, 2014) and facilitates germ cells progression to spermatozoa and in the nourishment of developing sperm cells (Griswold, 1998, 2018; Liang et al., 2019). Testicular activities of LDH, ALP and ACP are important in the maintenance of normal germ cell growth and phosphorylative role in glucose usage by germ cells during spermatogenesis (Akhigbe & Ajayi, 2020; Motawi, Sadik, & Refaat, 2010; Rizk, Zaki, & Mina, 2014), while G6PD is essential for providing reducing equivalent necessary for steroidogenesis (Aly & Khafagy, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Nr5a1 is required for all three steps. By applying a similar experimental design, Liang et al [ 34 ] revealed that two genes, NR5A1 and GATA4 , are sufficient for the direct reprograming of human fibroblasts to Sertoli cells. Moreover, under the same concept, Yang et al [ 35 ] successfully reprogramed mouse fibroblasts directly to Leydig cells using Nr5a1 , Gata4 , and Dmrt1 .…”
Section: Potential For Nr5a1/nr5a1 To Be a Key Genmentioning
confidence: 99%
“…Some have overexpressed transcription factors to directly reprogram mouse or human fibroblasts into Sertoli and Leydig-like cells ( Buganim et al., 2012 ; Jadhav and Jameson 2011 ; Yang et al., 2015 , 2017 ; Yazawa et al., 2006 ). The ectopic expression of the transcription factors GATA4 and NR5A1 appears to be sufficient to reprogram human fibroblasts into Sertoli-like cells ( Liang et al., 2019 ). Other protocols have used co-cultures of human and mouse cells ( Rodríguez Gutiérrez et al., 2018 ; Shlush et al., 2017 ; Yamashiro et al., 2018 ) or co-cultures of human iPSCs with NT2D1 cells to differentiate Sertoli-like cells ( Rodríguez Gutiérrez et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%